Legal Protection for Policyholders Against PT Asuransi Jiwa Kresna's Default based on the Supreme Court Decision No. 647 K/Pdt.Sus-Pailit/2021 - Amanda Lanisya; Faisal Santiago (Greenation Research & Yayasan Global Resarch National, 2025)
Based on Decision Number 389/Pdt.Sus-PKPU/2020/PN Niaga Jkt.Pst (Decision 389), policyholders of PT Asuransi Jiwa Kresna (PT AsJK) were considered applicants for a Posponement of Indebtedness Payout Responsibility (PeKPU) and therefore had special legal protection through homologation. However, according to Supreme Court Verdict Num. 647 K/Pdt.Sus-Pailit/2021 (MA Decision 647), the homologation was declared null and void, thus unprotected policyholders, and the Financial Services Authority (OJK) never permitted it. According to MA Decision 647, policyholder protection against PT AsJK's default is the objective of this research. This normative legal research uses secondary data collected through library research. The research results indicate that because insurance policyholders lack legal status as applicants for a PeKPU against insurance companies, the legal protection provided by MA Decision 647cannot protect insurance policyholders. OJK is the only party that allows PeKPU applications. However, based on the Decision 389, OJK has been granted protection even though the Commercial Court Panel of Judges has set aside the OJK's legal conviction as a PeKPU applicant.